Developing an integrated care pathway to connect home-based palliative care and emergency departments: participatory action research on a quality improvement project. - Rubrigi, Lorenzo (Acta Biomedica Atenei Parmensis, 2024)
This study presents a participatory action-research framework aimed at improving the integration of palliative care (PC) in emergency departments (EDs). The research describes the development and implementation of a clinical pathway for PC patients accessing emergency services in Modena, Italy. Through a mixed-methods approach, including interviews, questionnaires, and observational data, the study outlines the participatory process, the resulting clinical pathway, and baseline measures. Key findings include active engagement of healthcare professionals in pathway development, successful training initiatives, and the establishment of a structured approach to PC in the ED. The study emphasizes the importance of participatory approaches in addressing complex healthcare challenges and highlights the need for ongoing evaluation of integrated PC models in emergency settings.